Thermal dehydration kinetics and characterization of synthesized potassium borates - Ortega Asensio, Miguel; Yildirim, Meral; Senberber, Fatma Tugce; Kipcak, Azmi Seyhun; Derun, Emek Moroydor (SPRINGER, 2016)
In this study, potassium pentaborate (santite: KB5O8 center dot 4H(2)O), with a powder diffraction number of 01-072-1688 was synthesized from potassium carbonate (K2CO3), boric acid (H3BO3) and boron oxide (B2O3) with reaction efficiencies between 84.88 and 95.11 %, through a hydrothermal route. Reaction temperatures and times were varied between 60-90 A degrees C and 15-120 min. Synthesized minerals were characterized by X-ray diffraction, Fourier transform infrared and Raman spectroscopies, while surface morphologies were determined by scanning electron microscopy. Thermal dehydration behavior of santite was determined by thermal gravimetry and differential thermal analysis. From the results, santite lost its crystal water via a two-step process between 50 and 450 A degrees C. Activation energies (E (a)) were calculated by using four non-isothermal kinetic methods and found to be 110.12 and 202.43 kJ/mol by the Coats-Redfern method, 107.77 and 304.18 kJ/mol by the Doyle method, 158.82 and 154.50 kJ/mol by the Kissinger-Akahira-Sunose method, and 158.07 and 156.76 kJ/mol by the Ozawa-Flynn-Wall method for the steps 1 and 2, respectively.
Keywords: Hydrothermal; Non-isothermal kinetic; Potassium borate; Thermal dehydration; THERMOGRAVIMETRIC DATA; SINGLE-CRYSTALS; FLUIDIZED-BED; PENTABORATE; GROWTH; GLASS; TUNELLITE; TITANIUM; MINERALS; ULEXITE; Chemistry